Share Whatever You Like - Böhm, Sebastian; Koolwaaij, Johan; Luther, Marko (Electronic Communications of the EASST, 2008)
To leverage proactive context-aware services for mobile handsets, an for the management, aggregation and distribution of information is required. This work presents a framework that has been developed to realize an extensible infrastructure in which personal information can be shared with others while on the go. Access control mechanisms restrict the distribution of data based on social relationships and the validity of context conditions.